Effect of pre- and post- processing upon shot-peening residual stresses - Rasul, Tahir (Cranfield University, 1989)
The overall aim of the present investigation is to adopt a fundamental approach towards the identification, measurement and modelling of the effect of pre- and post-processing upon shot-peening residual stresses. At present this is carried out in an ad hoc fashion with little understanding of the fundamental properties which are being affected by these treatments and of how these basic properties influence product performance and determine (the peening) process parameters. Indeed, current concern of reliability and efficiency of machinery alone justifies the widespread interest in the present investigation. The specific objectives arising from the above overall aim can be summarised as follows: (i) to identify, measure and model the effect of pre-processing upon the locked-in residual stress field and surface morphology of a prospective peening component, (ii) to identify, measure and synthesize the effect of shot-peening treatment upon the resulting stress field and surface profile of the treated component, (iii) to identify, measure and model the effect of post-processing upon the aforementioned parameters, and (iv) to examine the effect of residual stresses and incomplete-coverage upon ultimate product performance. Consideration of the surface profile will be accounted for in the analysis. The outcome of these investigations should provide the foundation necessary for process control and optimisation of working surfaces of components currently employed in aerospace, automotive and power generation industries. Accordingly a number of investigations will be carried out, in parallel, to highlight these effects. In view of the large number of variables involved in these processes, we focus our attention to the following: for pre-processing, controlled turning was selected and for post-processing, controlled grinding was selected. Residual stress measurements were performed by the centre hole air-abrasive off-centre rotating nozzle method, and whenever possible, the results were verified by other methods such as X-ray diffraction and etching. An experimental rig was designed, built and commissioned to allow for locating different sizes and shapes of cylindrical and flat components accurately near the 'drilling head'. The surface topography was measured, using a motorised stage and a profilometer of the stylus type. This arrangement enabled the three dimensional determination of treated surfaces. The materials investigated were typical of aircraft alloys: steel 817M40 and aluminium 7075, which were provided by a major landing-gear manufacturer (Dowty Rotol) . In order to examine the effect of residual stresses and surface profile upon ultimate product performance, fatigue tests using electro-hydraulic servo-controlled test equipment were used to evaluate the effect of the treatment upon the fatigue life and relaxation of residual stresses. Both complete and incomplete coverage were considered in the analysis. The results of the work show that pre-processing can induce unfavourable tensile residual stresses, which are detrimental to the fatigue life of the component. They also show that peening residual stresses play an important role ~n negating these tensile residual stresses. Effects of surface profile due to the pre-treatment also indicated a major influence on the success of the treatment, and upon the selection of the appropriate peening parameters. As for post-processing, it was shown that the residual stresses varied linearily with depth removed and remained significant even after 50 percent of the arc height had been removed from the component.